Side Chain Redistribution as a Strategy to Boost Organic Electrochemical Transistor Performance and Stability. Issue 37 (5th August 2020) - Moser, Maximilian; Hidalgo, Tania Cecilia; Surgailis, Jokubas; Gladisch, Johannes; Ghosh, Sarbani; Sheelamanthula, Rajendar; Thiburce, Quentin; Giovannitti, Alexander; Salleo, Alberto; Gasparini, Nicola; Wadsworth, Andrew; Zozoulenko, Igor; et al.
Abstract: A series of glycolated polythiophenes for use in organic electrochemical transistors (OECTs) is designed and synthesized, differing in the distribution of their ethylene glycol chains that are tethered to the conjugated backbone. While side chain redistribution does not have a significant impact on the optoelectronic properties of the polymers, this molecular engineering strategy strongly impacts the water uptake achieved in the polymers. By careful optimization of the water uptake in the polymer films, OECTs with unprecedented steady‐state performances in terms of [ μC * ] and current retentions up to 98% over 700 electrochemical switching cycles are developed. Abstract : A series of polythiophenes for use in organic electrochemical transistors (OECTs) differing only in the distribution of the side chains that are tethered to the conjugated backbone is presented. By optimization of the water uptake in the polymers, OECTs with [ μC * ] over 500 F cm −1 V −1 s −1 and current retentions up to 98% over 700 electrochemical switching cycles are presented.